The Influence of Animated Video Media on the Knowledge and Attitudes of Adolescent Girls in Preventing Stunting at SMAN 1 Tempuling (HEALTH CARE: JURNAL KESEHATAN, 2025)
Background: Stunting is a serious problem because it is associated with the risk of morbidity and mortality in children, poor brain and motor development and delayed mental development. An animated video is a combination of audio and visuals from a collection of moving image objects, so that an image object is created that looks real and seems more lively and attracts attention. Purpose: To determine the influence of animated video media on the knowledge and attitudes of female adolescents in preventing stunting at SMAN 1 Tempuling. Methods: The research method used is Quasi experimental design. In this research there are two groups, namely the experimental group and the control group. This research was carried out at SMAN 1 Tempuling, Sungai Salak Village, Tempuling District, Indragiri Hilir Regency in May 2024-June 2024. The sample of respondents in this research was 124 respondents using quota sampling technique The results of the research show that the animated video media for preventing stunted births for young women is declared feasible and is expected to help in efforts to reduce the prevalence of stunting. Results: The results of statistical tests using simple linear regression analysis in the experimental group obtained a significance value (p) of 0.00 which was smaller than α 0.05 so that there was a relationship between the animated video and the students' knowledge and attitude variables. In the T test, a significance value (p) of 0.00 was obtained, meaning that the independent variable (animated video) had an influence on the dependent variable (knowledge and attitudes). Conclusion: There is a significant relationship between animated videos on students' knowledge and attitudes with a value of P 0.00 which is smaller than P 0.05